Effets thérapeutiques de la coquille d’oeuf - Azizi, Djilali; Latouche, Touati (My University, 2022)
The problem of waste explicitly illustrates our overconsumption of resources, placing a heavy responsibility on institutions, This study was carried out at the level of the Willaya of Mostaganem, the main objective of which is to know the possibility of valuing eggshells as a source of calcium and a large number of very useful minerals to strengthen and protect the body. And the different uses of eggshells by the population of Mostaganem in therapy, through a questionnaire ask 50 people at different ages from 20 to 60 years old woman and man,the study shows that the use of eggshells is increased in women compared to men, as well as women use eggshells in cosmetics and also for therapeutic purposes as a calcium supplement. Our study also shows that the supplementation of eggshells in the food ration according to the population is done to treat fractures and wounds. This survey reveals that eggshell waste is sought for therapeutic purposes by the local population of the study area.
Keywords: Eggs; Ration; Shell; Calcium supplement; Therapy